Removing two transition metal ions from spiked wastewater by two modified nano-sorbents. Issue 1 (31st December 2022) - Abdallah, Maha Ahmed Mohamed
Abstract: Biosorption is an extensive technology applied for the removal of heavy metal ions and other pollutants from aqueous solutions. In the present study, the sorption of metal ions from the polluted huge drain (El Tapia drain) in Abu Qir Bay was determined using nano-magnetic iron oxide and nano-silver oxide, low cost and eco-friendly nano-sorbents, which shows a high potential for metal (Cd and Ni) uptake due to the small size of the nano-sorbents, which is favorable for the diffusion of metal ions from the solution onto the active sites of the adsorbent surface. Therefore, Fe3 O4 and silver oxide Ag2 O nanosorbents can be effective and economical adsorbents for the rapid removal and recovery of metal ions from aqueous media. In this study, we will synthesize magnetic active and silver oxide adsorbents and marine biomass-coated magnetic and silver composites and evaluate their effectiveness for the removal of toxic metals from one hot spot on the Alexandria coast. uf0001